POLICY ON OVERCOMING VILLAGE BUDGET DEVIATIONS BY THE GOVERNMENT INTERNAL SUPERVISORY APPARATUS IN INDONESIA (CASE STUDY OF TANJUNGSARI VILLAGE, LAMPUNG) - I Ketut Seregig; Bambang Hartono; Yustina Ndari (Universitas Lampung, 2021)
Corruption is deeply rooted in Indonesia. This fact is undeniable when this crime has occurred at the lowest government level, namely in the village government. One sample of cases raised in this study is the alleged Corruption Crime committed by the Head of Tanjungsari Natar Village, South Lampung, named Robangi. The problems examined in this alleged criminal act are the factors causing the perpetrator to commit the criminal act of corruption. Second, the pattern of countermeasures carried out by APIP in resolving the case. The method used is qualitative and in the research data collection using a normative juridical approach and empirical juridical. Meanwhile, the theory used as a knife of analysis is the theory of Non-Penal Policy proposed by Muladi and Barda Nawawi Arief, which states that